Antioxidant, Transcriptomic and Metabonomic Analysis of Hepatopancreatic Stress Resistance in Exopalaemon carinicauda Following Astaxanthin Feeding - Li, Wenyang; Wang, Jiajia; Li, Jitao; Liu, Ping; Li, Jian; Zhao, Fazhen (Frontiers in Marine Science, 2022)
Astaxanthin (Axn) is a xanthophyll carotenoid that has previously been shown to suppress hepatic inflammation, reduce oxidative liver damage, and improve metabolic profiles. Exopalaemon carinicauda (E. carinicauda) is an economically important fishery species in China that has been found to exhibit increased body weight following Axn feeding as compared to a standard diet. In this study, dietary Axn can significantly decreased MDA content and significantly increased T-AOC, SOD, GSH and CAT activities in shrimp hepatopancreas. Moreover, transcriptome and metabolome of E. carinicauda after Axn feeding were investigated to identify the mechanism of the effect of Axn on E. carinicauda. The transcriptomic data revealed that a total 99 different expression genes (DEGs) were identified between the Axn and control groups, of which 47 and 52 were upregulated and downregulated, respectively. DEGs of E. carinicauda after Axn feeding were associated with apoptosis and immune system. The metabolomic analysis revealed that A total of 73 different expression metabolites (DEMs) were identified in both metabolites, including 30 downregulated metabolites and 43 upregulated metabolites. And Axn participate in metabolism processes in hepatopancreas of E. carinicauda, including the TCA cycle, amino acid metabolism and lipid metabolism. The multiple comparative analysis implicated that Axn can improve the antioxidant capacity of hepatopancreas and the energy supply of hepatopancreas mitochondria, and then improve the ability of anti-apoptosis. Collectively, all these results will greatly provide new insights into the molecular mechanisms underlying tolerance of adverse environment in E. carinicauda.